Thermal Stress Analysis of Maxillary Dentures with Different Reinforcement Materials Under Occlusal Load Using Finite Element Method - Semih Benli; Gökhan Baş (Applied Sciences)
The purpose of this study was to determine the effect of fiber reinforcement materials on the magnitude of stresses in a critical part of the maxillary denture base under thermal and occlusal load. Thermal stress analyses of the models were carried out using the finite element method. The models consisted of bone, soft tissue, interface gap, and maxillary dentures with and without reinforcements. A concentrated occlusal load of 230 N was applied bilaterally on the molar teeth. A 36 °C reference and 0 °C, 36 °C, and 70 °C variable ambient temperatures were applied to the models. CrCo, unidirectional and woven carbon/epoxy, unidirectional and woven glass/epoxy, and unidirectional and woven Kevlar/epoxy were used as reinforcing materials in the maxillary denture base made of PMMA (polymethyl methacrylate). Stress distributions on the maxillary denture’s midline and lateral line direction were evaluated. Maximum stresses in the incisal notch and the labial frenal notch of the maxillary denture were determined. Failure analysis of reinforcement materials used in maxillary dentures was carried out using the Tsai-Wu index criterion. The results obtained show that the thermal properties of reinforcement materials should be considered as an important criterion in their selection.